The right heart in cardiac amyloidosis: a comparison between subtypes and with other genetic and non-genetic causes of left ventricular hypertrophy. (25th November 2020) - Palmiero, G; Rubino, M; Monda, E; Caiazza, M; Trinchillo, M.G; Ascione, L; Caso, P; Limongelli, G
Abstract: Background: Right chambers involvement is common in cardiac amyloidosis (CA) but has been ever compared to control groups. Purpose: Aim of this study is to compare right heart involvement between CA subgroups (AL vs. ATTR amyloidosis) and between CA and other forms of genetic and non-genetic left ventricular hypertrophy. Methods: We enrolled 25 patients with CA (10 pts with AL and 15 pts with wild type ATTR amyloidosis) and 75 patients with LVH (25 HCM pts; 25 HypCMP pts; 25 AS pts). Beside routine echocardiographic measurements, we analysed right chambers dimensions and classical and novel parameters for right ventricular (RV) function [TAPSE (Tricuspid Anulus Plane Systolic Excursion), St (S' wave at RV TDI), global and free-wall strain]. Results: ATTR group showed higher right dimensions compared to AL, without differences in RV systolic parameters (see table). CA patients, compared to LVH group, showed no differences in right dimensions. RV systolic parameters were significantly reduced while diastolic Doppler parameters were higher (E/E' 21.7±9.0 vs. 11.2±5.0; p<0.0001). At ROC curve analysis TAPSE showed the best ability in discriminating CA among other forms of LVH (AUC 0.936; 95% CI: 0.879–0.993; p<0.0001), with a sensibility of 94.7% and specificity of 87.3% for a cut-off value of 19.5 mm. At Kaplan-Meier estimation CA patients showed a significantly higher cardiovascular mortality compared to LVH group (9/25 deaths vs. none). At multivariate analysis TAPSE was the only independent prognostic factor (β 1.324; 95% IC: 1.086–1.614; p<0.006). Discussion: CA group showed a significantly impaired RV systolic function with higher pulmonary pressures compared to LVH group. TAPSE proved to be the only able to discriminate CA among genetic and non-genetic forms of LVH and also to have prognostic significance. Funding Acknowledgement: Type of funding source: None